Experimental Study on the Influence of Type of Stirrup of Prestressed Concrete Beams with Corroded Rebars - Fang-Yuan Li; Liu-Yang Li; Wen-Hao Li; Peifeng Wu (Advances in Civil Engineering)
Corrosion of longitudinal reinforcement and stirrup in reinforced and prestressed concrete beams is very common for structures and infrastructures, which is one of the main reasons for the decrease in stiffness and durability of structure. In order to evaluate the influence of corrosion of different types of stirrups on the bearing capacity of the prestressed concrete beam, the method of using electricity to accelerate corrosion was adopted. Load experiment on 4 corroded prestressed concrete beams with different corrosion rates and different stirrup types was carried out. In this paper, reduced scale model beams were designed based on the 5 × 50 m simple-continuous box girder of the Donghai Bridge. The results show that for prestressed concrete beams with different corrosion rates and stirrup types, the load-deflection curve can be divided into an elastic stage and a plastic stage. The corrosion of longitudinal bars and stirrups will reduce the flexural capacity, but the overall decline is not obvious. When the corrosion rate is 10%, the bearing capacity of the ordinary stirrup specimen decreases by 6.1%; epoxy-coated stirrup specimen decreases by 4.9%; stainless stirrup specimen has nearly no change. The influence of different types of stirrups on cracking load, deflection, and bond-slip behavior is discussed.